2017
DOI: 10.2147/amep.s138278
|View full text |Cite
|
Sign up to set email alerts
|

Online nutrition and T2DM continuing medical education course launched on state-level medical association

Abstract: ObjectiveThe purpose of this research study was to determine whether a 1-hour online continuing medical education (CME) course focused on nutrition for type 2 diabetes would result in a gain in nutrition knowledge by practicing physicians.MethodsA practicing physician and dietitian collaborated to develop an online CME course (both webinar and self-study versions) on type 2 diabetes. This 1-hour accredited course was launched through the state-level medical association’s education library, available to all phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…Moreover, online CME programs keep physicians updated about current diabetes guidelines [ 37 ]. Similar to our finding, Hicks & Murano (2017) concluded lifestyle-focused online CME programs improved knowledge of physicians [ 27 ]. In addition, recent studies emphasized the success of online video-based CME on improving knowledge of primary care physicians related to diabetes management and insulin therapy [ 38 , 39 ].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Moreover, online CME programs keep physicians updated about current diabetes guidelines [ 37 ]. Similar to our finding, Hicks & Murano (2017) concluded lifestyle-focused online CME programs improved knowledge of physicians [ 27 ]. In addition, recent studies emphasized the success of online video-based CME on improving knowledge of primary care physicians related to diabetes management and insulin therapy [ 38 , 39 ].…”
Section: Discussionsupporting
confidence: 90%
“…Beaser et al (2013) recommended a new approach for diabetes-focused CME and emphasized performance improvement CME [ 46 ]. A recent publication reported that a one-hour online CME course can assist practicing physicians in addressing patient nutrition and lifestyle concerns related to type 2 diabetes [ 27 ]. Similar to the current research, this publication reported the positive impact of a single online diabetes-focused CME on physicians’ knowledge; however, the sample size in the reported study was low (especially concerning GPs and medical internists) and covered various areas of practice specialties and nutrition-focused CME on Type 2 diabetes [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many activities focusing on HCP education in the management of T2D have been developed. Although some peer-reviewed publications have described outcomes from educational activities in diabetes, these are highly heterogeneous, may include patients with type 1 diabetes, and may include a range of activities and a variety of end points [9,10,[14][15][16][17][18][19][20].…”
Section: Education In T2d Managementmentioning
confidence: 99%
“…This course effectively improved nutrition knowledge relating to type 2 diabetes management among physicians and awareness of the role of the RDN. (32) Virtual seminars may be an effective tool to disseminate nutrition information to medical students as well. (33) However, in the context of medical school and CMEs, challenges exist with virtual learning such as a lack of audience engagement.…”
Section: Current Interprofessional Collaborationmentioning
confidence: 99%